Variations in perceptions of urban and rural health promotion competencies - Shilton, T.; Lower, Anthony; Howat, Peter; James, Raymond (Australian Health Promotion Association, 2003)
Issue addressed: To identify perceptions of essential competencies by rural and urban-based health promotion practitioners. Methods: Data were collected using two rounds of a Delphi to rank competencies as either not relevant, aspecific competency relevant to some but not all health promotion practitioners, a desirable or essentialcompetency. The sample consisted of members of the Australian Health Promotion Association (AHPA) and the Public Health Association of Australia (PHM) Special Interest Group in health promotion. A snowballing technique was also used to increase rural representation. Results: Two rounds of the Delphi resulted in 207 duplicate responses, 148 (72%) urban and 57 (27%) rural. Rural practitioners were significantly more likely to perceive the skills required to implement health promotion strategies as essential (t=-2.4, p=O.015). Statistically significant competencies in rural areas included media skills, research/evaluation skills and use of information technology. Conclusions: There are some significant variations in the perceived essential competencies required by rural health promotion practitioners.